2004
DOI: 10.1189/jlb.0404219
|View full text |Cite
|
Sign up to set email alerts
|

The role of γδ T cells in the regulation of neutrophil-mediated tissue damage after thermal injury

Abstract: Thermal injury induces an inflammatory response that contributes to the development of secondary tissue damage. Neutrophil recruitment and activation are in part responsible for this tissue damage. Although gammadelta T cells have been shown to regulate the inflammatory responses in tissues that are prone to neutrophil-mediated injury post-burn, their role in the induction of secondary tissue injury post-burn remains unknown. To study this, gammadelta T cell-deficient (gammadelta TCR-/-) and wild-type (WT) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 57 publications
3
50
1
1
Order By: Relevance
“…5D, 5E). The ability of pThy-derived dermal gd T cells to recruit inflammatory cells, such as neutrophils, is likely due to their production of IL-17 (16,20,42), and recruitment of neutrophils by gd T cells directly results in increased tissue damage (43). We demonstrated increased necrosis and cellularity of infected ears 3 d after VV infection, indicating that the resident IL-17 + gd T cells are early responders to viral infection.…”
Section: Cd27mentioning
confidence: 67%
“…5D, 5E). The ability of pThy-derived dermal gd T cells to recruit inflammatory cells, such as neutrophils, is likely due to their production of IL-17 (16,20,42), and recruitment of neutrophils by gd T cells directly results in increased tissue damage (43). We demonstrated increased necrosis and cellularity of infected ears 3 d after VV infection, indicating that the resident IL-17 + gd T cells are early responders to viral infection.…”
Section: Cd27mentioning
confidence: 67%
“…[24][25][26] It has been well demonstrated that HSP70, also called stress protein, may participate in the cellular response to hyperthermia, ischemic injury, infection and autoimmune diseases. [27][28][29][30] The protein serves as a chaperone molecule for various intracellular proteins and may alter their functional characteristics. The induction of HSP70 expression by bacterial infection has a role in the cellular response to injury.…”
Section: Discussionmentioning
confidence: 99%
“…The role of cd cells has not been yet totally elucidated but beside their protective immunity against infections and tumors, immunoregulation is an emerging paradigm of their function. For instance, in liver and mucosal surfaces, these T cells have regulatory roles such as initiating or inhibiting inflammation [15,17,26] and they contribute to macrophage homeostasis [13,27]. Whether they play such roles in adipose tissues remains to be elucidated.…”
Section: Characterization Of Lymphocytes In White Adipose Tissuesmentioning
confidence: 99%